Acceptance of upper airway muscle training for treatment by obstructive sleep apnea: Results of a prospective survey. Issue 1 (2nd January 2018) - Li, Wen-Yang; Gakwaya, Simon; Series, Frederic
ABSTRACT: RATIONALE: Obstructive sleep apnea (OSA) is associated with a variety of adverse health outcomes. Upper airway muscle training (UAMT) may represent a novel, effective treatment approach for OSA. OBJECTIVE: This study aimed to quantify the proportion of OSA patients who would consider UAMT and to investigate the influential physiological and sociodemographic factors. METHODS: A total of 158 consecutive newly diagnosed OSA patients were recruited to complete a self-administered survey, including assessment of their interest towards upper airway muscle training, anticipated ability to complete it and factors that could influence these attitudes. Sociodemographic information and sleep recording data were also obtained. RESULTS: The majority of patients were interested in such program (82.9%) and mentioned their ability to complete it 1 hour/day for 1 month (72.1%), especially if applied later only 2–3 times/week (82.9%). A total of 55.0% of them indicated that requirements of training schedule and duration might influence their choice. Patients with low socioeconomic status (SES) were more prone to complete such program 2–3 times/week when compared with high SES group (p < 0.05). Multivariate analysis revealed that age (OR: 1.04, 95% CI: 1.01–1.07; P = 0.02) was an independent determinant for interest to complete UAMT therapy. ODI (OR: 0.95, 95% CI: 0.94–1.00; P = 0.04) predicted preference for UAMT over the overnight-used conventional devices. CONCLUSIONS: This study demonstrates that the majority of OSA patients are interested in such therapy, suggests their ability to complete it, along with a preference over conventional therapies. The aforementioned attitudes are sensitive to gender, age, severity of disease and socioeconomic status. RÉSUMÉ: JUSTIFICATION: L'apnée obstructive du sommeil (AOS) est associée à divers effets néfastes sur la santé. La rééducation des muscles des voies respiratoires supérieures pourrait être un traitement novateur et efficace pour l'AOS. OBJECTIF: Cette étude visait à quantifier la proportion de patients atteints d'AOS qui envisageraient la rééducation des muscles des voies aériennes supérieures et à examiner les facteurs physiologiques et sociodémographiques influents. MÉTHODES: 158 patients consécutifs ayant récemment obtenu un diagnostic d'apnée obstructive du sommeil ont été recrutés afin de répondre à un questionnaire auto-administré évaluant leur intérêt pour la rééducation des muscles des voies respiratoires supérieures, leur capacité à suivre ce traitement jusqu'au bout, ainsi que les facteurs qui pourraient influencer ces attitudes. Les données sociodémographiques et les données d'enregistrement du sommeil ont aussi été obtenues. RÉSULTATS: La majorité des patients étaient intéressés à ce programme (82, 9 %) et ont dit être capables de le suivre une heure par jour pendant un mois (72, 1 %), en particulier s'il devait être appliqué seulement deux à trois par semaine par la suite (82, 9 %). 55 % d'entre eux ont indiqué que les exigences de l'horaire et la durée de la rééducation pourraient influencer leur choix. Les patients de statut socioéconomique faible étaient plus enclins à suivre ce programme deux à trois fois par semaine comparativement au groupe de statut socioéconomique plus élevé (p < 0, 05). Une analyse multivariée a démontré que l'âge (RC: 1, 04, 95 % IC: 1, 01 – 10, 07; P = 0, 02) était un déterminant indépendant de l'intérêt à suivre le traitement de rééducation des muscles des voies aériennes supérieures. L'IDO (RC: 0, 95, 95 % IC: 0, 94 – 1, 00; P = 0, 04) était prédicteur d'une préférence pour la rééducation des muscles des voies aériennes supérieures par rapport aux appareils conventionnels utilisés toute la nuit. CONCLUSIONS: Cette étude démontre que la majorité des patients atteints d'apnée obstructive du sommeil sont intéressés à ce traitement. Elle suggère aussi qu'ils sont aptes à le suivre jusqu'au bout et qu'ils le préfèrent aux traitements conventionnels. Les attitudes ci-dessus sont sensibles au genre, à la gravité de la maladie et au statut socioéconomique.